Evaluation of POME sludge as organic soil amendments on the growth performance and yield of Brassica rapa subsp. chinensis L. - Yusop, Zubaidah; Sahmat, Siti Sahmsiah; Mahdian, Suraiya; Wan Yusuf, Sharifah Mazenah; Jos, Syahira (Universiti Teknologi MARA, Sarawak, 2025)
Palm oil mill effluent (POME) sludge is a nutrient-rich organic byproduct with potential application in sustainable agriculture. However, limited information about POME sludge deserves serious attention since its application in agriculture could enhance plant growth and productivity. This study assesses the effects of raw POME sludge and alginate-encapsulated POME sludge as soil amendments on the growth and productivity of Brassica rapa subsp. chinensis L. A field experiment was conducted using a Completely Randomized Design with three treatments: control (no amendment), POME sludge, and POME sludge encapsulated with sodium alginate. Key agronomic parameters including plant height (cm), chlorophyll content (SPAD), leaf width (cm), shoot and root biomass, total yield (g), and shoot-to-root ratio were measured at biweekly intervals. Statistical analysis was performed using ANOVA and post-hoc least significant difference (LSD) tests at p < 0.05. The results indicated no significant differences in plant height, SPAD, or leaf width among these treatments. In contrast, yield, shoot biomass, and shoot-to-root ratio were significantly improved, with the highest values observed in the alginate-encapsulated POME sludge treatment. Yield increased from 154.00 g in the control to 340.16 g in the encapsulated treatment. Correlation analysis further supported strong associations between shoot biomass, yield, and shoot-to-root ratio. The findings demonstrate that alginate-encapsulated POME sludge is an effective organic amendment for enhancing yield and biomass accumulation in Brassica rapa subsp. chinensis L. production.